2003
DOI: 10.1152/ajpheart.00270.2003
|View full text |Cite
|
Sign up to set email alerts
|

Adrenomedullin gene delivery attenuates myocardial infarction and apoptosis after ischemia and reperfusion

Abstract: delivery attenuates myocardial infarction and apoptosis after ischemia and reperfusion. Am J Physiol Heart Circ Physiol 285: H1506-H1514, 2003. First published June 12, 2003 10.1152/ ajpheart.00270.2003 has been shown to protect against cardiac remodeling. In this study, we investigated the potential role of AM in myocardial ischemiareperfusion (I/R) injury through adenovirus-mediated gene delivery. One week after AM gene delivery, rats were subjected to 30-min coronary occlusion, followed by 2-h reperfusion.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
84
3

Year Published

2004
2004
2008
2008

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 122 publications
(97 citation statements)
references
References 42 publications
10
84
3
Order By: Relevance
“…Importantly, in an in vivo rat model of ischemia and reperfusion, AM attenuates myocardial infarction and apoptosis [31]. This effect is caused through increase in Akt and Bad phosphorylation and Bcl-2 levels [31]. Our present results in prostate cancer cells also demonstrate that AM induces the expression of Bcl-2 and decreases Bax, which favours the anti-apoptotic signaling and prevents the cells from undergoing apoptosis.…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…Importantly, in an in vivo rat model of ischemia and reperfusion, AM attenuates myocardial infarction and apoptosis [31]. This effect is caused through increase in Akt and Bad phosphorylation and Bcl-2 levels [31]. Our present results in prostate cancer cells also demonstrate that AM induces the expression of Bcl-2 and decreases Bax, which favours the anti-apoptotic signaling and prevents the cells from undergoing apoptosis.…”
Section: Discussionsupporting
confidence: 64%
“…Bcl-2 and AM are co-expressed in cervical cancer [30]. Importantly, in an in vivo rat model of ischemia and reperfusion, AM attenuates myocardial infarction and apoptosis [31]. This effect is caused through increase in Akt and Bad phosphorylation and Bcl-2 levels [31].…”
Section: Discussionmentioning
confidence: 99%
“…15 In a rat myocardial ischemia/reperfusion injury model, gene delivery of AM suppressed ROS production by NADPH oxidase inhibition via the nitric oxide (NO)-cGMP signaling pathway. 23 In addition, because AM induced vasodilation because of increased cAMP and NO overproduction 24 and endothelin-1 downregulation, 25 AM-induced reduction of shear stress might be involved in reducing ROS production. But we performed no hemodynamic studies.…”
Section: Discussionmentioning
confidence: 99%
“…Our previous study showed that systemic delivery of the kallikrein gene inhibited I/R-induced myocardial injury, which was accompanied by increased kinin and cGMP levels (22). Similarly, adrenomedullin gene transfer also increased cardiac cGMP levels after I/R (23). cGMP is an indicator of nitric oxide formation, and these results indicate that the nitric oxide-cGMP signaling cascade may serve as the common signaling cascade for cardioprotective stimuli in the injured myocardium.…”
mentioning
confidence: 83%
“…Preparation of Replication-deficient Adenoviral Vectors-Adenoviral vector harboring the human tissue kallikrein cDNA (Ad.CMV-TK) under the control of the cytomegalovirus (CMV) enhancer/promoter or adenoviral vector alone (Ad.Null) were constructed and prepared as described previously (23). Adenoviruses containing the dominant-negative mutant of Akt (Ad.DN-Akt), constitutively active Akt (Ad.MyrAkt), catalytically inactive GSK-3␤ (Ad.GSK3␤-KM) and constitutively active mutant of GSK-3␤ (Ad.GSK3␤-S9A) were kindly provided by Dr. Kenneth Walsh, St. Elizabeth's Medical Center in Boston.…”
Section: Methodsmentioning
confidence: 99%